Supercritical fluid chromatography: a promising alternative to current bioanalytical techniques. (January 2018) - Dispas, Amandine; Jambo, Hugues; André, Sébastien; Tyteca, Eva; Hubert, Philippe
During the last years, chemistry was involved in the worldwide effort toward environmental problems leading to the birth of green chemistry. In this context, green analytical tools were developed as modern Supercritical Fluid Chromatography in the field of separative techniques. This chromatographic technique knew resurgence a few years ago, thanks to its high efficiency, fastness and robustness of new generation equipment. These advantages and its easy hyphenation to MS fulfill the requirements of bioanalysis regarding separation capacity and high throughput. In the present paper, the technical aspects focused on bioanalysis specifications will be detailed followed by a critical review of bioanalytical supercritical fluid chromatography methods published in the literature. Graphical abstract: